Soft skills and the impact of covid-19 on higher education - Vásquez-Pajuelo, Lida (2021)
This research paper seeks to know how to promote the development of soft skills in order to face successfully the impacts on higher education of the post-pandemic period. The study is based on an exhaustive review of current literature on soft skills and the promotion of their development in students. Such promotion will allow students to improve their soft skills and become aware of their own socio-emotional qualities. In the future, accordingly, they will be able to be part of a generation of professionals capable of having a harmonious emotional development, which includes moments of high work pressure. Higher education should foster among its community members, especially among students, the different means for expanding soft skills, with the consequent positive impacts on their future employment. Soft skills should be understood as those skills that enhance interaction between one another; strengthen relationships; and improve relationships and emotional control in work, professional and personal environments. The methodology applied in this study is qualitative in nature, and consists of both , reviewing current research, and collecting data from different authors that explain what “soft skills”mean.